التكاليف الاقتصادية للاحتلال الإسرائيلى على الشعب الفلسطينى - United Nations Conference on Trade; Development (United Nations, 2020)
This study identifies and assesses existing and potential Palestinian oil and natural gas reserves that could be exploited for the benefit of the Palestinian people that Israel is either preventing them from exploiting or is exploiting itself without due regard to international law.